Analisis Keefektifan Penggunaan Filter FIR dan IIR pada Sinyal Pernapasan EMGdi dengan Simulasi MATLAB - Christopher Leonard; Nabila Husna Shabrina (Ultima Computing : Jurnal Sistem Komputer, 2020)
Medical instrumentations are used to retrieve and record signal data in the patient’s body such as respiratory signals. The data from the respiratory signal is able to diagnose the patient’s respiratory health. Unfortunately, in retrieving signal data, there are noises that interfere with the required signal information. In this article, the signal input will be filtered with two types of filter (FIR filter with window method and IIR filter with pole-zero placement method or bilinear transformation method) and compared their effectiveness to reduce or eliminate the noise signal. Both filters have a cut-off frequency of 50 Hz. The outputsignal shows that the noise ECG signal is more effective to be eliminated with an IIR filter because of its characteristic filter. Therefore, the IIR filter is morerecommended being used in medical instrumentation for its effectiveness and minimum hardware required.